2010
DOI: 10.1097/ajp.0b013e3181ed1058
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Infant Pain Assessment Using Heart Rate Variability Analysis

Abstract: The results of this study indicate that postoperative pain is associated with a decreased high-frequency HRV in full-term newborn infants. Our findings suggest that HRV could be used as an indicator to assess prolonged pain in the newborn infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 31 publications
2
98
0
9
Order By: Relevance
“…One study found that our method had a low sensitivity and specificity for postoperative acute-pain evaluation [26] ; yet, a majority of data indicate that our technology allows anesthetists to adapt analgesia during surgical procedures, labor, and postoperative recovery time [22-24, 26, 35] . We have also demonstrated that this method can be used to assess pain and discomfort in newborn and preterm infants [27] . This study is the first step in evaluating the ability of our method to assess fetal distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that our method had a low sensitivity and specificity for postoperative acute-pain evaluation [26] ; yet, a majority of data indicate that our technology allows anesthetists to adapt analgesia during surgical procedures, labor, and postoperative recovery time [22-24, 26, 35] . We have also demonstrated that this method can be used to assess pain and discomfort in newborn and preterm infants [27] . This study is the first step in evaluating the ability of our method to assess fetal distress.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the ability of our index to investigate the autonomic response to painful stimuli in adults (both conscious and unconscious) [22][23][24][25][26] . We have also demonstrated that our method can be used to assess pain and discomfort in newborn and preterm infants [27] . Recent studies have highlighted that this method can also be used for the accurate prediction of the occurrence of hypoxemia [28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ağlama, kol ve bacak hareketleri, yüz kiriştirma, tonus değişiklikleri, inleme, huzursuzluk ve beslenme güçlüğü davranişsal tepkilerdendir [14,15]. Ağri sirasinda kalp atim hizinda artiş, solunumda değişiklikler ve oksijen satürasyonunda düşme fizyolojik belirtiler arasindadir [14,16]. Biyokimyasal tepki olarak; kortizol, katekolamin, büyüme hormonu, glukagon, renin ve aldesteron salgilanmasi artar, insülin salgilanmasi ise azalmaktadir [7,14,15,17,18].…”
Section: Uluslararasiunclassified
“…Nous avons évalué la VFC chez des nouveau-nés admis après un geste chirurgical. L'indice mesuré était significativement plus bas chez les enfants qui avaient un score d'EDIN élevé [14]. Dans une autre étude, nous avons évalué la VFC chez des nouveau-nés à la naissance après une extraction instrumentale : la VFC était significativement plus basse chez les enfants ayant un score d'EDIN élevé [15].…”
Section: Introductionunclassified